The untranslatability of a text and the non-equivalence of words: Непереводимость текста и безэквивалентность слов - Alekseyeva, Maria; Pavlova, Anna V. (Przegląd Wschodnioeuropejski, 2020)
This article deals with the current state of development of two main categories of modern translation theory: “untranslatability” and “non-equivalence”. Untranslatability belongs to translation-theoretic universals and is a binary category. The essence of the phenomenon, its nature, as well as such concepts as “translation losses”, “untranslatable units”, “translatological classification of text types” are considered. The differences in the meaning of the concepts “untranslatability” and “non-equivalence” are described. The article objective is to show actuality and pecularity of their manifistation in the context of the Russian and German languages.